2016
DOI: 10.17795/jjnpp-28749
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Ametryn From Aqueous Solutions With Zeolite Nanoparticles Optimized Using the Box-Behnken Design

Abstract: Background: Nowadays, adsorption techniques are widely used to remove certain classes of pollutants from water. Objectives: The aim of this study was to remove ametryn from water solutions by natural zeolite nanoparticles from the Semnan region of Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(37 reference statements)
0
1
0
2
Order By: Relevance
“…The properties of the nanoparticles were evaluated, and a Box-Behnken response surface methodology was applied to investigate all parameters affecting the adsorption mechanism continuously. The results demonstrated that at a temperature of 43 • C, pH 6, 2 g of adsorbent, and a contact time of 2 h, the nanoparticles were able to degrade 64.12% of ametryn in the water samples [192]. At optimum conditions, nanoparticles performed well and efficiently degraded 80% of atrazine in an aqueous solution with a short retention time of 20 min.…”
Section: Nano-remediation Of S-triazine Herbicidesmentioning
confidence: 94%
“…The properties of the nanoparticles were evaluated, and a Box-Behnken response surface methodology was applied to investigate all parameters affecting the adsorption mechanism continuously. The results demonstrated that at a temperature of 43 • C, pH 6, 2 g of adsorbent, and a contact time of 2 h, the nanoparticles were able to degrade 64.12% of ametryn in the water samples [192]. At optimum conditions, nanoparticles performed well and efficiently degraded 80% of atrazine in an aqueous solution with a short retention time of 20 min.…”
Section: Nano-remediation Of S-triazine Herbicidesmentioning
confidence: 94%
“…Este herbicida é utilizado em mais de 45 países, sendo que o Brasil é o maior consumidor, seguido por Tailândia, México, Chile e Cuba (Lebaron, 2011). Esse agrotóxico é amplamente utilizado como herbicida seletivo para o controle de folhas largas e gramíneas invasoras em culturas agrícolas de milho, cana-deaçúcar, banana e abacaxi e existem poucas informações sobre seus efeitos subletais (Khodayar et al 2016;Navaratna et al 2012).…”
Section: Ametrinaunclassified
“…Como resultado da alta toxicidade, mutagenicidade e carcinogenicidade das substâncias químicas contidas em pesticidas, o acúmulo aleatório no meio ambiente representa séria ameaça para os ecossistemas e para a saúde humana (Khodayar et al, 2016;Morillo & Villaverde, 2017;Xu et al, 2009).…”
Section: Ametrinaunclassified